ENTREPRENEUR CHARACTERISTICS AND MANAGEMENT COMPETENCY TOWARD AGRICULTURAL COOPERATIVE ORGANIZATIONAL SUCCESS IN THAILAND: Received: 21st March 2022; Revised: 02nd June 2022, 01st July 2022; Accepted: 05th July 2022 - Keerati-angkoon, Kanyakit (PEOPLE: International Journal of Social Sciences, 2022)
The purpose of this study was to examine the effects of entrepreneurial characteristics and management competency on the consequence factors of operation success of Agricultural Co- operative in Thailand. Questionnaires were used as a tool and mailed to sample groups and 357 of them were returned. To analyze the data, multiple regression analysis was used. The results of the study showed the following: 1) Entrepreneur characteristics including leadership, interpersonal relations, taking risks, and goal setting affected to the successful Agricultural Co-operative organizational; 2) the diversity of management competency includes good operation systems, accounting, and financing systems, and technology management, all affected the Agricultural Co-operative organizational success, too. Therefore, enterprises should set systems to work in organizations especially accounting and financing systems, along with adopting information technology for managing an organization. In addition, managers should improve entrepreneurial skills in leadership, interpersonal relations, and risk-taking for achievement and increased competitive advantage.